2021
DOI: 10.1155/2021/7656834
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline Extends the Lifespan of C. Elegans and Delays the Progression of Age‐Related Diseases by Activating AMPK, DAF‐16, and HSF‐1

Abstract: Trigonelline is the main alkaloid with bioactivity presented in fenugreek, which was used in traditional medicine in Asian countries for centuries. It is reported that trigonelline has anti-inflammatory, anti-oxidant, and anti-pathogenic effects. We are wondering whether trigonelline have anti-aging effect. We found that 50 μM of trigonelline had the best anti-aging activity and could prolong the lifespan of Caenorhabditis elegans (C. elegans) by about 17.9%. Trigonelline can enhance the oxidative, heat, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Superoxide dismutases ( SOD ‐3) encoded by gene sod‐3‐ in CF1553. These SOD ‐3 enzymes play a fundamental role in protecting the cells from oxidative stress and prolonging lifespan (Zeng et al, 2021). Oxidative stress is one of the leading causes of P.D., as we mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutases ( SOD ‐3) encoded by gene sod‐3‐ in CF1553. These SOD ‐3 enzymes play a fundamental role in protecting the cells from oxidative stress and prolonging lifespan (Zeng et al, 2021). Oxidative stress is one of the leading causes of P.D., as we mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that trigonelline at different concentrations could prolong the healthy lifespan, enhance the locomotor ability and reduce the accumulation of lipofuscin in the body in C. elegans. Moreover, trigonelline was also able to delay the progression of age-related diseases in C. elegans models of AD, PD, and HD [36].…”
Section: Herbsmentioning
confidence: 95%
“…Meanwhile, trigonelline reduced the loss of neurons by inhibiting oxidative stress, astrocyte activity and inflammation and also protecting mitochondrial integrity (Chowdhury et al, 2018; Fahanik‐Babaei et al, 2019). Zeng et al (Zeng et al, 2021) showed that trigonelline could prolong the life of Caenorhabditis elegans by 17.9%, enhance the antioxidant capacity of elegans, regulate the expression of some genes,and finally delay the development of neurodegenerative diseases.…”
Section: Anti‐ad Active Ingredients In Plantsmentioning
confidence: 99%